Celosten pristop k polnovredni rastlinski prehrani - Jakše, Boštjan (Šport (Ljubljana), 2021)
The increasingly popular plant-based diet presents a challenging change for many in today's modern lifestyle - both in terms of introducing it and maintaining it in the long term. There are several motives for such a diet, usually associated with weight management and health benefits or ethical reasons. People who decide on changing their diet face many challenges. Some of these challenges are related to the (i) disapproval of whole-food, plant-based diet by the "profession", associated with the (ii) characteristics of a whole-food, plant-based diet, some with the (iii) need for acquiring new skills and some with a (iv) muchneeded supportive environment. Here, a comprehensive ongoing support system can play a very important role, since it can offer a personalized and proven process of change for every individual. Such a model makes it easier for an individual to change a dietary behaviour into a new habit, make sense of it and live a healthy and active lifestyle in a tolerant manner to people with different dietary patterns. A well-planned whole-food, plant-based diet enables people an efficient control over their appetite, which is one of the main reasons for unsuccessful weight loss with popular weight-loss diets. Today, a comprehensive approach to a whole-food, plant-based diet is a well-founded and proven model. The majority of energy should be invested in efficient methods of informing and raising awareness about the benefits, potential risks and, consequently, the responsibility for a proper implementation of a plant-based diet and finding sustainable business models that are available to a broader audience.
Keywords: active life; aktivno življenje; food; lifestyle; način življenja; plant-based diet; polnovredna rastlinska prehrana; prehrana; sistem podpore; sport; support system; šport; whole-food